The Effect of Disaster Training on Teachers Candidates' Perception of Disaster Awareness - Serap Yılmaz Özelçi; Celalettin Çelebi (Sakarya University, 2024)
Turkiye frequently experiences disasters that negatively affect human life in terms of various aspects. Therefore, teacher candidates who will teach future generations should be educated about raising disaster awareness. In this study, the effect of the disaster awareness training given by AFAD on the disaster perceptions, and awareness levels of teacher candidates were studied. In the research convenience sampling method was adopted. 58 teacher candidates, 44 females and 14 males, participated in the study which was designed in the "Single Group Pre-Test - Post-Test" model. Teacher candidates took disaster training for 12 hours in two courses. After the training, there was a partial increase in disaster awareness levels. However, the results showed that having received disaster training before or having experienced a disaster did not make a significant difference in disaster awareness. A disaster education course, including practice, can be integrated into undergraduate programs of education faculties.